Integrated Transcript and Metabolite Profiles Reveal That EbCHI Plays an Important Role in Scutellarin Accumulation in Erigeron breviscapus Hairy Roots - Chen, Ruibing; Chen, Xianghui; Zhu, Tingting; Liu, Jianghua; Xiang, Xing; Yu, Jian; Tan, Hexin; Gao, Shouhong; Li, Qing; Fang, Yichao; Chen, Wansheng; Zhang, Lei; et al. (Frontiers in Plant Science, 2018)
Scutellarin, a flavonoid 7-O-glucuronide, is an essential bioactive compound of Erigeron breviscapus (Vaniot) Hand.-Mazz. used for the treatment of cerebrovascular diseases. However, due to overexploitation and overuse, Erigeron breviscapus is facing the problems of extinction and habitat degradation. In this study, a correlation analysis between the transcript and metabolite profiles of MeJA-treated E. breviscapus at different time points indicated that chalcone isomerase (EbCHI) was the primary contributor to scutellarin accumulation during flavonoid biosynthesis. EbCHI was then further characterized as a chalcone isomerase that efficiently converted chalcone to naringenin in vitro. Optimal parameters derived by comparing different culture conditions were successfully used to establish hairy root cultures of E. breviscapus with a maximum transformation rate of 60% in B5 medium. Furthermore, overexpression of EbCHI significantly enhanced scutellarin accumulation in E. breviscapus hairy roots with a maximum content of 2.21 mg g-1 (dw), 10-fold higher than that of natural roots (0.21 mg g-1 dw). This study sheds new light on a method of effective gene-based metabolic engineering by accurate and appropriate strategies and provides a protocol for hairy root cultures that accumulate high levels of scutellarin, providing a promising prospect for relieving the overexploitation and unavailability of E. breviscapus in the future.